2019
DOI: 10.1002/glia.23715
|View full text |Cite
|
Sign up to set email alerts
|

A modified flavonoid accelerates oligodendrocyte maturation and functional remyelination

Abstract: Myelination delay and remyelination failure following insults to the central nervous system (CNS) impede axonal conduction and lead to motor, sensory and cognitive impairments. Both myelination and remyelination are often inhibited or delayed due to the failure of oligodendrocyte progenitor cells (OPCs) to mature into myelinating oligodendrocytes (OLs). Digestion products of the glycosaminoglycan hyaluronan (HA) have been implicated in blocking OPC maturation, but how these digestion products are generated is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Stem cell therapy using bone marrow mesenchymal stem cells (BMSCs) is a promising therapeutical advance in the recent decade. Several studies have shown that BMSCs might exert certain functions on the oligodendrocyte precursor cells (OPCs), the progenitor cells of mature oligodendrocytes (OLs), and promote their enrichment to the sites of injury, differentiation and remyelination of the damaged nerve fibers [12][13][14]. For example, in vitro co-culture of OPCs with BMSCs has been found to preferentially drive the differentiation of OPCs into oligodendrocytes (oligodendroglial fate) rather than the astrocytes (astroglial fate) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell therapy using bone marrow mesenchymal stem cells (BMSCs) is a promising therapeutical advance in the recent decade. Several studies have shown that BMSCs might exert certain functions on the oligodendrocyte precursor cells (OPCs), the progenitor cells of mature oligodendrocytes (OLs), and promote their enrichment to the sites of injury, differentiation and remyelination of the damaged nerve fibers [12][13][14]. For example, in vitro co-culture of OPCs with BMSCs has been found to preferentially drive the differentiation of OPCs into oligodendrocytes (oligodendroglial fate) rather than the astrocytes (astroglial fate) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell therapy using bone marrow mesenchymal stem cells (BMSCs) is a promising therapeutical advance in the recent decade. Several studies have shown that that BMSCs might exert certain functions on the oligodendrocyte precursor cells (OPCs), the progenitor cells of mature oligodendrocytes (OLs), and promote their enrichment to the sites of injury, differentiation and remyelinating the damaged nerve bers [9][10][11]. For example, in vitro co-culture of OPCs with BMSCs has been found to preferentially drive the differentiation of OPCs into oligodendrocytes (oligodendroglial fate) rather than the astrocytes (astroglial fate) [12,13].…”
mentioning
confidence: 99%
“…Very recently, Su and colleagues developed a modified flavonoid (called S3) that potently and selectively inhibits the enzymatic activity of PH20 but not Hyal1 or Hyal2. S3 treatment was able to improve OPC maturation in vitro in presence of HMW HA and to promote functional remyelination in the LPC-induced demyelination model [106], suggesting that selective hyaluronidase inhibitors can be exploited to foster endogenous remyelination following CNS injuries. Several flavonoids (i.e., apigenin and hesperidin) have been shown to exert neuroprotective and immunomodulatory activity in the EAE model [107,108], suggesting that flavonoids can be potentially used as therapeutic compounds to counteract dysfunctional processes causing demyelination.…”
Section: Hyaluronanmentioning
confidence: 97%